Clinical utility of existing and second-generation interferon-γ release assays for diagnostic evaluation of tuberculosis: an observational cohort study - Whitworth, H; Badhan, A; Boakye, A; Takwoingi, Y; Rees-Roberts, M; Partlett, C; Lambie, H; Innes, J; Cooke, G; Lipman, M; Conlon, C; Macallan, D; et al. (Elsevier, 2019)
Background The clinical utility of interferon-γ release assays (IGRAs) for diagnosis of active tuberculosis is unclear, although they are commonly used in countries with a low incidence of tuberculosis. We aimed to resolve this clinical uncertainty by determining the accuracy and utility of commercially available and second-generation IGRAs in the diagnostic assessment of suspected tuberculosis in a low-incidence setting. Methods We did a prospective cohort study of adults with suspected tuberculosis in routine secondary care in England. Patients were tested for Mycobacterium tuberculosis infection at baseline with commercially available (T-SPOT.TB and QuantiFERON-TB Gold In-Tube [QFT-GIT]) and second-generation (incorporating novel M tuberculosis antigens) IGRAs and followed up for 6–12 months to establish definitive diagnoses. Sensitivity, specificity, positive and negative likelihood ratios, and predictive values of the tests were determined. Findings Of the 1060 adults enrolled in the study, 845 were included in the analyses and 363 were diagnosed with tuberculosis. Sensitivity of T-SPOT.TB for all tuberculosis diagnosis, including culture-confirmed and highly probable cases, was 81·4% (95% CI 76·6–85·3), which was higher than QFT-GIT (67·3% [62·0–72·1]). Second-generation IGRAs had a sensitivity of 94·0% (90·0–96·4) for culture-confirmed tuberculosis and 89·2% (85·2–92·2) when including highly probable tuberculosis, giving a negative likelihood ratio for all tuberculosis cases of 0·13 (95% CI 0·10–0·19). Specificity ranged from 86·2% (95% CI 82·3–89·4) for T-SPOT.TB to 80·0% (75·6–83·8) for second-generation IGRAs. Interpretation Commercially available IGRAs do not have sufficient accuracy for diagnostic evaluation of suspected tuberculosis. Second-generation tests, however, might have sufficiently high sensitivity, low negative likelihood ratio, and correspondingly high negative predictive value in low-incidence settings to facilitate prompt rule-out of tuberculosis.